Erotic Narration of Syair Lebai Guntur - Mustari Mustari (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The text of Syair Lebay Guntur contained in the Syair Lebay Guntur text by Raja Ali Haji records the traces of the 'disgraceful' behavior of some Malay people in the past who practiced "Cina Buta" marriages. It is aiming to find muhallil or a proponent to reconcile a couple (wife and husband) who had divorced by triple divorce. Because the problem raised in the poetry is a matter of muhallil, inevitably, its diction appears to be erotic in every verses of the poetry. This study employed the theory of diction and language style with stylistic analysis of Malay to uncover two raised problems they are (1) Can erotic diction contained in SLG be categorized as vulgar pornography? (2) How to interpret the erotic diction? The findings show that the erotic diction in Syair Lebai Guntur poem cannot be categorized as pornography diction, but it rather as a diction adapted to the poem's theme of the practice of "Cina Buta" marriage. The diction considered as an allusion that is intended as teaching values which is not need to be copied by anyone to avoid a disgrace.